DETEKSI DINI KANKER PAYUDARA DENGAN SADARI DAN SADARNIS - Arianggara, Andi Wilda; Sulaiman, Yulianah; Rasmawati; Fadhilah , Nur (Awal Bros Journal of Community Development, 2024)
Breast cancer is a contributor to a fairly high mortality rate in women, with a mortality rate of 18% of female deaths. Breast cancer in Indonesia is more likely to be detected at an advanced stage because public awareness of risk detection and early detection of breast cancer symptoms is still low. This Community Service aims to improve community knowledge and skills in preventing and early detection of breast cancer through counseling on breast cancer and breast self-examination training (SADARI). This Community Orientation was held on June 6, 2024 at the STIKes Bina Bangsa Majene Hall with lectures, discussions, questions and answers, and demonstrations. The participants in this community service are 33 people. The result of this activity is to increase the knowledge and skills of participants related to how to detect breast cancer early with SADARI and SADARNIS.